Multinational companies and human resource management in Ireland during recession: A retrospective from a highly globalized economy. (7th May 2018) - Gunnigle, Patrick; Lavelle, Jonathan; Monaghan, Sinéad
Abstract : This article provides a retrospective investigation of the impact of the recent "great recession" on human resource management (HRM) in multinational companies (MNCs) in Ireland. Ireland represents a particularly fitting location within which to address this topic given its standing as one of the world's most economically globalized and MNC‐dependent economies and also because the country was very severely impacted by the global financial crisis. Using both primary and secondary data from a variety of sources, our analysis considers the impact of recession on HRM in MNCs, with particular focus on employment, pay and benefits, industrial relations, and the role of the human resource (HR) function. The findings suggest that HR practitioners played a central role in implementing a series of initiatives, many of which were operational in nature, to improve business performance. In so doing, we argue that practitioners in MNCs in Ireland behaved as archetypical "conformist innovators" during the recent recession, delivering operational HR responses to improve their organization's bottom line.